What kind of mathematics is needed to be a future manager? - Saldauskienė, Jovita (Lietuvos matematikos rinkinys, 2010)
This article deals with relevant problems of mathematics’ subject studies in college. Perceptions of the subject of mathematics teaching for social sciences programms students are discussed. The present analysis reveals further directions of mathematics quality improvement search.
Keywords: applied mathematics; programs; students; studies